Mental health support within professional soccer academies: clarifying the roles of psychologists, player care staff and clinicians - James, Ian A.; Turner, Martin James (Frontiers in Psychology, 2025)
Surveys of professional soccer players mental health (MH) difficulties reveal a prevalence either equal or higher compared to the general population. It is suggested that under reporting of problems occurs because of the stigma associated with disclosing difficulties, poor MH literacy, and concerns about deselection. This paper presents a stepped-care pathway of MH support, together with a discussion about the optimal manner by which this support can be provided. While suggesting that enhancing the MH of players is ‘everyone’s business’, particular focus is given to the work of sports psychologists (SP), members of the player care team, and specialist MH clinicians. The use of such a pathway is discussed within a professional soccer club, and issues about communication, confidentiality and competition are debated. The pros and cons of employing a qualified MH clinician within a club are also discussed, as well as the conditions required for such an appointment to work effectively.